What Triggers Streamflow for Intermittent Rivers and Ephemeral Streams in Low‐Gradient Catchments in Mediterranean Climates. Issue 11 (28th November 2019) - Gutiérrez‐Jurado, Karina Y.; Partington, Daniel; Batelaan, Okke; Cook, Peter; Shanafield, Margaret
Abstract: Intermittent rivers and ephemeral streams (IRES) account for over 50% of the world's river network and are expected to increase with climate change and the increasing pressure on water resources. One significant challenge to better manage IRES is unraveling the threshold behavior of streamflow generation, by understanding what controls the triggers of streamflow. This study aimed to understand the influence of groundwater depth, soil hydraulic properties, and rainfall on streamflow generation in IRES, through analyzing the spatiotemporal development of active areas (where flow generation processes are occurring) and determining the dominant flow generation mechanisms. In a concept‐development approach, we used fully Integrated Surface‐Subsurface Hydrological Models to investigate streamflow generation for a range of characteristics representative of IRES in low‐gradient catchments with Mediterranean climates. The results showed that soil type exerts the greatest overall influence on streamflow generation and is the main factor determining the spatiotemporal development of active areas by a given flow generation mechanism and threshold contributing processes. The identified dominant mechanism for each soil demonstrated the effect of the initial groundwater head and rainfall scenarios on the timing and processes that trigger streamflow onset. These results reaffirm the importance of unsaturated storage dynamics to explain thresholds and pathways of flow and suggest that knowledge of the development of active areas and prediction of the dominant flow generation mechanisms is critical to understand streamflow generation in IRES. Future research should identify the influence of catchment morphology, geologic constraints, and aquifer heterogeneity and anisotropy on streamflow generation in IRES. Plain Language Summary: "Temporary rivers" is a broad term used to classify waterways that are dry for some part of the year. They contribute roughly 50% of all the world's available river water, are important for groundwater replenishment, and maintain key environmental services. To manage them, we need to understand how they transition from a dry to a flowing state. In this study, we use computer models to explore how rainfall, soil properties, and the depth to groundwater affect the processes that trigger when this transition occurs. We tested over 1, 600 scenarios to explore the effect of different factors on when, where, and why these rivers will flow. Results showed that soil type was the main control determining when and where flow is generated and is the governing factor dictating the different ways water gets to the river. For this, we identified distinct pathways that water takes to get to the river for each of the tested soils. Understanding the different pathways in which water moves through the catchment can help manage vulnerability of temporary rivers to the impacts of land use changes, soil erosion, and prolonged droughts. Future studies should investigate the effects of catchment morphology and heterogeneity on streamflow generation in IRES. Key Points: Soil type controls streamflow generation and determines the spatiotemporal development of active areas and dominant flow generation mechanisms The dominant flow generation mechanism is Dunne overland flow for sand, Horton overland flow for sandy loam, and interflow for sandy gravel Pathways and thresholds of flow generation are visible from the development of active areas by a given flow generation mechanism